Pengaruh Media Pembelajaran Kahoot Terhadap Motivasi Belajar Bahasa Arab Siswa Di MTS. Al-Qur’an Terpadu An-Nawawi Surabaya - Moh. Syaifudin; Firdausi Nurharini; Hadyan Diaz Ramadhan (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
The problems in this study are the low motivation of students learning Arabic through kahoot media, the lack of implementation of the Arabic language learning process with a kahoot learning environment and whether the kahoot learning media influences student learning motivation. The purpose of this study was to determine students' learning motivation towards the learning process with the help of kahoot learning media, to determine the implementation of learning Arabic with the help of a kahoot learning environment and to determine the effect of students' use of kahoot media. on student motivation. This study was conducted at the Integrated Al-Qur'an An-Nawawi Surabaya by MT on Jl. Srengganan Lebar No. 30-32, Sidodadi, Kec. Simokerto, Surabaya City, East Java 60145. The population of this study were all students of class VIII MTs Al-Qur'an An-Nawawi, namely. 14 students and the sample includes the entire population. There is a difference in the average score between the experimental class and the control class, where the experimental class that uses kahoot learning media has a higher average score of 86.43 and tends to experience a significant increase compared to the control class with an average learning score of more low 65.71.